Physical performance, body composition and somatotype in Colombian judo athletes - Monterrosa Quintero, A.; Bet da Rosa Orssatto, L.; Pulgarin, L. D.; Follmer, B. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2019)
Background. Judo is a grappling sport that requires a combination of powerful actions (e.g., throwing techniques) and aerobic capacity. Physical performance, body composition and somatotype influences athletes` performance. Problem and aim. Analyze the physical performance, body composition and somatotype of elite Colombian judokas and compare them with athletes from other countries. In addition, to investigate the correlation between body composition and physical performance. Methods. Fifteen judoists, eight women (21±4.7 years) and seven men (20.5±3.9 years), participated in the present study. The athletes were black belt and had international and national competition experience, winning medals in the Pan-American Games, Central and South American Championships. Squat jumps (SJ) and countermovement jumps (CMJ) on a contact platform were performed to evaluate lower limbs power. The maximum oxygen uptake (VO2max) was estimated using the multistage 20-m shuttle run test. The Anthropometric measurements were taken for body fat and skeletal muscle mass estimation. Pearson correlation was performed between body composition and physical performance variables. Results. In summary, lower physical performance, and higher body fat percentages were observed in Colombian judoists compared to elite judoists. In other countries Moderate negative correlation was observed between aerobic power and body fat percentage (r=-0.67), and the endomorph characteristic (r=-0.69). In addition, the skeletal muscle mass presented a very large correlation with power from both SJ (r=0.88) and CMJ (r=0.89) (p<0.05). Conclusion. Elite Colombian judokas presented lower physical performance, and higher body fat percentage than other elite judokas. The somatotype was adequate and in accordance with that reported at the elite level.